Brief encounters: Assembling cosmetic surgery tourism. (January 2015) - Holliday, Ruth; Bell, David; Cheung, Olive; Jones, Meredith; Probyn, Elspeth
Abstract: This paper reports findings from a large-scale, multi-disciplinary, mixed methods project which explores empirically and theoretically the rapidly growing but poorly understood (and barely regulated) phenomenon of cosmetic surgery tourism (CST). We explore CST by drawing on theories of flows, networks and assemblages, aiming to produce a fuller and more nuanced account of – and accounting for – CST. This enables us to conceptualise CST as an interplay of places, people, things, ideas and practices. Through specific instances of assembling cosmetic surgery that we encountered in the field, and that we illustrate with material from interviews with patients, facilitators and surgeons, our analysis advances understandings and theorisations of medical mobilities, globalisation and assemblage thinking. Highlights: Presents findings from a major multi-disciplinary project. Provides in-depth analysis of cosmetic surgery tourism industry. Develops a theoretical framework based around flows, networks and assemblages. Illustrated with qualitative data from Tunisia, Poland, Thailand and South Korea.